2022
DOI: 10.3390/children9091317
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Vulnerable Children Well-Being: Interview with Left-Behind Children in Rural China

Abstract: Purpose of the study: This study sought to explore the psychological well-being, academic adjustment, and quality of parental attachment of LBC during COVID-19 based on Left-Behind Children’s (LBC) word of mouth. Method: In light of the abundance of quantitative studies, this qualitative study explored the psychological, academic, and parental attachment experiences of rural LBC during COVID-19. To this end, we conducted semi-structured interviews with 22 LBCs aged 10–15 in May 2021. Result: The study results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…According to the authors, some of the caregivers used singing of gospel hymns and prayer for coping whenever they nd themselves in predicament aggravated by execution of caring tasks among children orphaned by HIV/AIDS. Similar results were reported by the study conducted in Ethiopia caregivers put God rst in everything that they were doing and di culties that confronted them in caring for orphaned children [43].…”
Section: Context (In What Context Is the Conceptual Framework Perform...supporting
confidence: 85%
See 1 more Smart Citation
“…According to the authors, some of the caregivers used singing of gospel hymns and prayer for coping whenever they nd themselves in predicament aggravated by execution of caring tasks among children orphaned by HIV/AIDS. Similar results were reported by the study conducted in Ethiopia caregivers put God rst in everything that they were doing and di culties that confronted them in caring for orphaned children [43].…”
Section: Context (In What Context Is the Conceptual Framework Perform...supporting
confidence: 85%
“…They had hope that through him everything is possible he cannot leave his children to suffer without providing solutions to their problems [43]. The ndings of this study, together with those from earlier research, demonstrate the necessity of having trust and hope in God and the necessity of involving him in whatever we do daily.…”
Section: Context (In What Context Is the Conceptual Framework Perform...supporting
confidence: 54%
“…In this study, the total score of SCL-90 of left-behind children during the pandemic was observed to be higher than the national norm (130.02 ± 33.63), 16 indicating the overall poor mental health status of left-behind children during the pandemic, and the results are consistent with those of previous studies. 11 , 12 , 17 Conversely, the SCL-90 score of left-behind children after the pandemic was lower than the national norm, which indicated that the mental health of left-behind children improved significantly after the pandemic compare with that during the pandemic. This result may be attributed to the cancellation of the closed stay policy after the pandemic, recovery of traffic roads, parents of left-behind children returning to their hometown, and the left-behind children feeling more loved and having a sense of security and trust compared with that during the pandemic.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, the total score of SCL-90 of left-behind children during the pandemic was observed to be higher than the national norm (130.02 ± 33.63), 16 indicating the overall poor mental health status of left-behind children during the pandemic, and the results are consistent with those of previous studies. 11,12,17 Conversely, the SCL-90 score of left-behind children after the pandemic was lower than the national norm, which indicated that the mental health of left-behind children…”
Section: Regression Analysis Of Mental Health Factors After the Pandemicmentioning
confidence: 94%
“…Moreover, developmental theories emphasize the significant impact of early experiences on individual development [8]. Conversely, parent-child separation during this period disrupts parenting practices and interactions, potentially leading to insecurity and ambiguous loss for children, which may contribute to adverse outcomes in mental health, social and academic achievement [1,[8][9][10]. Additionally, grandparents' parenting style and physical condition may limit their involvement and patience, affecting children's emotional regulation and the development of social skills [11,12].…”
Section: Introductionmentioning
confidence: 99%